(untitled) (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2021)
Conceptualization is one of the most important processes of human cognitive activity, which consists in understanding the information coming to it and leads to the formation of concepts, conceptual structures and the entire conceptual system in the human brain (psyche) [6, p.93]. Conceptualization is often considered as a "cross-cutting" process of knowledge structure for different forms of knowledge and the emergence of different structures of knowledge representation from some minimal conceptual units [4].